A strategy to achieve high-strength WNiFe composite-like alloys with low W content by laser melting deposition. (May 2020) - Zhou, Shangcheng; Wang, Lu; Liang, Yao-Jian; Zhu, Yichao; Jian, Ruizhi; Wang, Benpeng; Wang, Liang; Xue, Yunfei; Wang, Fuchi; Cai, Hongnian; Ren, Yang
Abstract: Preparing bulk WNiFe alloys with high strengths and low W content (<80 wt%) is challenging. Here, we present a strategy, powder-fed laser melting deposition (LMD), to solve this problem. The LMD-prepared WNiFe (LMD WNiFe) samples show high mechanical strengths and low W contents of 50 and 75 wt%. The W particles in the LMD WNiFe samples uniformly distribute in the matrix (γ), exhibiting fine particle sizes of approximately one-fifth of those of conventional 93WNiFe alloys prepared by liquid phase sintering (LPS). The ultimate tensile strengths of the 50 and 75 wt% samples are 1120 and 1316 MPa, respectively, which are 24.44 and 59.33% higher than those of the LPS-prepared 93WNiFe alloy (LPS 93WNiFe). These results suggest a useful strategy for preparing low-W-content, high-strength WNiFe alloys with fine, uniformly distributed W particles. This finding offers new potential applications of WNiFe alloys in additive manufacturing. Graphical abstract: Unlabelled Image Highlights: WNiFe with W particle size of 5.5 μm is prepared by laser melting deposition (LMD). WHAs with low W content (no W skeleton to keep shape) can be achieved by LMD. W particles in LMD WHAs distribute uniformly in γ matrix. The yield strength of LMD WHAs is 59.3% higher than that of LPS WHAs.